Focal lesions of the liver in the course of retroperitoneal fibrosis – case report and brief review of the literature - Kołodziej-Spirodek, Lilianna; Rusiecka, Agnieszka; Hunia-Pająk, Karolina; Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2015)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Retroperitoneal fibrosis, (RF) is a rare disease characterized by proliferation of pathological fibrous tissue in the retroperitoneum. Changes are mostly located around abdominal aorta, inferior vena cava and ureters. The fibrosis can also appear in untypical locations and reach other organs of abdominal cavity. Etiology of the disease is unknown, although it is supposed to be related to autoimmune processes. The major role in RF diagnostics play radiology and histopathology. The treatment is based on corticosteroids, immunosuppressive drugs and surgery. Prognosis depends on early diagnosis and implementation of a proper therapy. We present a case of 53 years old female patient with focal lesions within the liver in the course of the RF which have undergone significant regression in the course of glycocorticotherapy and brief review of the literature.